2019
DOI: 10.26444/aaem/109598
|View full text |Cite
|
Sign up to set email alerts
|

The impact of selected factors on acceptance of illness and life satisfaction among female residents of rural areas treated for osteoporosis

Abstract: The impact of selected factors on acceptance of illness and life satisfaction among female residents of rural areas treated for osteoporosis. Ann Agric Environ Med. 2019; 26(4): 592-599. AbstractIntroduction. Osteoporosis is a chronic condition with serious sequela, including primarily bone fractures, and impacts on almost all spheres of human life. It is important for patients undergoing treatment to accept their health status and feel satisfied with life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 22 publications
5
14
0
Order By: Relevance
“…Although in many studies there were no statistically significant differences in acceptance of illness with regard to gender (Staniszewska et al, 2017;Kowalska et al, 2019), there were some results that showed the mean values of acceptance of illness being lower in males (Jankowska-Polańska et al, 2016) or in females (Kazimierska-Zając et al, 2018). Furthermore, other researchers (Jankowska-Polańska et al, 2016;Sierakowska et al, 2017;Janiszewska et al, 2019) found that the level of acceptance of illness was significantly reduced with age. Finally, some studies have shown that the type of disease can act as a determining factor of life quality and acceptance of illness (Chabowski et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although in many studies there were no statistically significant differences in acceptance of illness with regard to gender (Staniszewska et al, 2017;Kowalska et al, 2019), there were some results that showed the mean values of acceptance of illness being lower in males (Jankowska-Polańska et al, 2016) or in females (Kazimierska-Zając et al, 2018). Furthermore, other researchers (Jankowska-Polańska et al, 2016;Sierakowska et al, 2017;Janiszewska et al, 2019) found that the level of acceptance of illness was significantly reduced with age. Finally, some studies have shown that the type of disease can act as a determining factor of life quality and acceptance of illness (Chabowski et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…However, it would be interesting to verify whether this relationship is not bidirectional, that is, whether meaning in life is not an independent variable and illness acceptance acts as a potential mediator. In fact, some studies (Jaworski et al, 2018;Chen et al, 2019;Janiszewska et al, 2019) have confirmed that a proper attitude toward illness may be of particular importance in the context of giving meaning to disease and may lead to effective functioning.…”
Section: Limitationsmentioning
confidence: 99%
“…Lower values on the AIS scale, and therefore the worse acceptance of the disease, were found in women with osteoporosis (22.2), patients on peritoneal dialysis (23.2), dialyzed patients (24), systemic connective tissue diseases (24.5), multiple sclerosis (24.2), epilepsy (25.1) and ulcerative colitis (29.7) (11,12,(18)(19)(20)(21)(22). Greater disability, also in mobility, is associated with a higher level of depression and poorer acceptance of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…By accepting their disease, patients are able to adapt to the limitations it imposes on them, maintain or regain their self-esteem and control over their life, as well as cultivate more positive emotions [7].…”
Section: Introductionmentioning
confidence: 99%